Pro-inflammatory macrophages suppress HIV replication in humanized mice and ex vivo co-cultures - Baroncini, Luca; Muller, Christina K. S.; Kadzioch, Nicole P.; Wolfensberger, Rebekka; Russenberger, Doris; Bredl, Simon; Mlambo, Tafadzwa; Speck, Roberto F. (Frontiers in Immunology, 2024)
Introduction Very little is known about the role of macrophages as immune mediators during natural HIV infection. Humanized mice are an extremely valuable in vivo model for studying HIV pathogenesis. However, the presence of murine mononuclear phagocytes in these models represents a significant limitation for studying their human counterpart. Therefore, we have developed a novel humanized mouse model that allows selective depletion of human myeloid cells at a time point of our choosing. Methods We genetically engineered human hematopoietic stem and progenitor cells (HSPCs) to express an inducible caspase-9 (iCas9) suicide system under a synthetic myeloid promoter. Using these HSPCs, we generated humanized mice. iCasp9 induction in vivo resulted in selective human myeloid cell death in this inducible human myeloid depletion (iHMD) mouse model. In addition, we co-cultured monocyte-derived macrophages with ex vivo HIV-infected PBMCs to further mechanistically investigate the effect of macrophages on HIV replication using flow cytometry, cytokine analysis, and RNA sequencing of both macrophages and CD4+ T cells. Results HIV infection induced a pro-inflammatory phenotype in HIV-infected humanized NSG mice during the early and late stages of HIV infection. Myeloid cell depletion in HIV-infected iHMD-NSG mice resulted in a rapid increase in HIV RNA replication, which was accompanied by a loss of pro-inflammatory cytokines. Co-culture of macrophages with ex vivo HIV-infected PBMCs reproduced their anti-HIV effects observed in vivo. Transcriptomic data showed macrophages upregulate antiviral cytokines and chemokines in co-culture, while inducing CD4+ T cells to upregulate HIV restriction factors and downregulate pathways involved in protein expression and cell replication. Discussion This study describes a novel role of macrophages as effector cells, both ex vivo and in vivo, acting against HIV replication and limiting disease progression.